Comparability and methodological adjustments of labor statistics: The case of the unemployment rate for Ecuador - Castillo, José Gabriel; Salas, Carla María (Estudios de Economía, 2018)
The national statistical institutes face permanently the need to reform and update the statistical criteria and instruments for labor market analysis, as well as to adapt international recommendations for measurement. These processes pose important challenges regarding the comparability of information, necessary to analyze the labor market dynamics. This study presents a consistent methodological approach for the splicing of labor market aggregates based on microeconomic information from household surveys. We analyze the case of the national unemployment rate for Ecuador; assess the potential alternatives for simulation and define a consistent selection criterion for the prognosis and splicing of the series.